Rhizomatic education and Deleuzian theory. (1st September 2016) - Harris, David
Abstract: Personal experience participating in a Community Massive Open Online Course (cMOOC) discussing rhizomatic education ( Rhizo15 ) helped to ground some of the theoretical issues connected with trying to 'apply' Deleuzian work to education. Notions of connectivity and community as a learning resource are compared with the more abstract notion of a rhizome as an n-dimensional network in Deleuze and Guattari; a Deleuzian critique of objectivism is seen as transcending the persistent dualism of objectivity and subjectivity; Deleuzian critique of consensual thinking is seen to be relevant to a perceived problem with 'group think'. A brief account of Semetsky's 'learning paradox' leads to discussion of the suitability of the cMOOC structure for handling challenging material: participation, solidarity and engagement are encouraged, but opportunities are limited to pursue demanding and disciplined readings of Deleuzian work by excluding the positive and enlightening aspects of pedagogic authority. An example from debates on concept maps shows some neglected possibilities.